2008
DOI: 10.1111/j.1365-2702.2008.02357.x
|View full text |Cite
|
Sign up to set email alerts
|

Existential aspects of living with addiction – Part II: caring needs. A hermeneutic expansion of qualitative findings

Abstract: Understanding and being able to identify patients' caring needs associated with existential aspects of living with addiction will enable nurses to provide professional care and promote patient's recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 67 publications
(124 reference statements)
2
46
0
3
Order By: Relevance
“…Currently, the conceptual understanding of spirituality has expanded to include connections amongst human beings, with nature and with their God [3,4] . This definition implies that, while spirituality is related to personal discovery and self-reflection, it also encompasses the ability to see beyond the self and become more than the physical person.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the conceptual understanding of spirituality has expanded to include connections amongst human beings, with nature and with their God [3,4] . This definition implies that, while spirituality is related to personal discovery and self-reflection, it also encompasses the ability to see beyond the self and become more than the physical person.…”
Section: Introductionmentioning
confidence: 99%
“…Being active, whether sober or drunk, gave the men meaning in life. A recent study found that a sense of meaning in life is a central part of the recovery process in individuals suffering from substance dependency disorders (Wiklund, 2008). Furthermore, it has been pointed out that men suffering from AD felt they were being cared for when professionals gave them room to actively combat temptations of alcohol and to expand the life sphere themselves (Thurang, Rydström, Bengtsson-Tops, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Wiklund (2008) pointed out that in order to make the life comprehensible and manageable, individuals suffering from substance dependency need to have their life under control in the recovery process. Exercising self-control is connected to power and is a part of the hegemonic masculinity (Connell, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…From a nursing perspective it is of importance both in practice and research to focus on the individual patient's suffering, well-being, and needs of care (Benner, 1984;Eriksson, 2006). In line with this perspective, previous studies within the area of treatment of individuals suffering from alcohol dependency have pointed out the necessity of capturing both the lived experiences of being cared for (Smith, 1998;Thurang, Palmstierna, Fagerberg, & Bengtsson-Tops, 2010;Wiklund, 2008) and issues related to aspects of gender (Bloomfield, Gmel, & Wilsnack, 2006;John, Alwyn, Hodgson, & Phillips, 2008). According to Skeggs (2000) and Connell (2007) gender is performed and constructed at the breakpoint of individual, societal, cultural, and economical aspects of the lived life.…”
mentioning
confidence: 93%
“…All these factors contribute to an ongoing process of circulation to various formations of gender both between and within individuals (Connell, 2007). Currently, there is a lack of studies that investigate the lived experiences of patients with alcohol dependency being cared for by advanced nursing professionals (Wiklund, 2008). The aim of the present study was to explore and illuminate the meaning of caring in advanced nursing for men with alcohol dependency, as narrated by men themselves.…”
mentioning
confidence: 99%